Antibacterial and antibiofilm activities of diphyllin against fish pathogens. (August 2020) - Thamburaj, Suman; Ramaraj, Elangomathavan; Sethupathy, Sivasamy; Kamalanathan, Chakkaravarthi; Raji, Atchudan; Rajasekharan, Satish Kumar
Abstract: Annihilation of biofilm forming bacterial pathogens is a challenging aspect in seafood and aquaculture industries. Microbes growing as biofilms cause deleterious effects on food products leading to food spoilage or loss of shelf life. As a measure to fight biofilms, agents that prevent/disrupt biofilms are recurrently screened. The study exemplifies the bactericidal and biofilm disruption potentials of a plant derived compound, diphyllin, against fish pathogens that colonizes Oreochromis mossambicus and Oreochromis niloticus. Precisely, diphyllin disrupted Salmonella typhi biofilms by triggering reactive oxidative species (ROS). Diphyllin-induced ROS had satisfactory correlation with S. typhi cell membrane damage and intracellular DNA degradation profiles providing a putative mechanistic model. In conclusion, the study identifies diphyllin as a therapeutic and dispersal agent aimed at biofilms formed by food-borne pathogens that persistently plague food processing and aquaculture settings. Highlights: Diphyllin exhibited potent bactericidal effect against several fish pathogens. Diphyllin prevented/disrupted Salmonella typhi biofilms. Diphyllin treatment also resulted in DNA and membrane damage. Overall, diphyllin seemed to achieve bacterial killing by ROS induction.